The Critical and Diverse Roles of CD4–CD8– Double Negative T Cells in Nonalcoholic Fatty Liver DiseaseSummary - Changying Li; Xiaonan Du; Zongshan Shen; Yunxiong Wei; Yaning Wang; Xiaotong Han; Hua Jin; Chunpan Zhang; Mengyi Li; Zhongtao Zhang; Songlin Wang; Dong Zhang; et al. (Cellular and Molecular Gastroenterology and Hepatology, 2022)
Background & Aims: Hepatic inflammation is a hallmark of nonalcoholic fatty liver disease (NAFLD). Double negative T (DNT) cells are a unique subset of T lymphocytes that do not express CD4, CD8, or natural killer cell markers, and studies have suggested that DNT cells play critical and diverse roles in the immune system. However, the role of intrahepatic DNT cells in NAFLD is largely unknown. Methods: The proportions and RNA transcription profiling of intrahepatic DNT cells were compared between C57BL/6 mice fed with control diet or methionine-choline–deficient diet for 5 weeks. The functions of DNT cells were tested in vitro and in vivo. Results: The proportion of intrahepatic DNT cells was significantly increased in mice with diet-induced NAFLD. In NAFLD mice, the proportion of intrahepatic TCRγδ+ DNT cells was increased along with elevated interleukin (IL) 17A; in contrast, the percentage of TCRαβ+ DNT cells was decreased, accompanied by reduced granzyme B (GZMB). TCRγδ+ DNT cell depletion resulted in lowered liver IL17A levels and significantly alleviated NAFLD. Adoptive transfer of intrahepatic TCRαβ+ DNT cells from control mice increased intrahepatic CD4 and CD8 T cell apoptosis and inhibited NAFLD progression. Furthermore, we revealed that adrenic acid and arachidonic acid, harmful fatty acids that were enriched in the liver of the mice with NAFLD, could induce apoptosis of TCRαβ+ DNT cells and inhibit their immunosuppressive function and nuclear factor kappa B (NF-κB) or AKT signaling pathway activity. However, arachidonic acid facilitated IL17A secretion by TCRγδ+ DNT cells, and the NF-κB signaling pathway was involved. Finally, we also confirmed the variation of intrahepatic TCRαβ+ DNT cells and TCRγδ+ DNT cells in humans. Conclusions: During NAFLD progression, TCRγδ+ DNT cells enhance IL17A secretion and aggravate liver inflammation, whereas TCRαβ+ DNT cells decrease GZMB production and lead to weakened immunoregulatory function. Shifting of balance from TCRγδ+ DNT cell response to one that favors TCRαβ+ DNT regulation would be beneficial for the prevention and treatment of NAFLD.